Family Support for Adherence to Routine Checkups in Patients with Diabetes Mellitus - Retno Sumara; Nugroho Ari Wibowo; Sindy Dwi Fitria Nilam Sari; Diah Priyantini (Indonesian Academia Health Sciences Journal, 2026)
Introduction: Diabetes mellitus (DM) is known as the “Mother of Diseases” among various incurable chronic conditions. Adherence to routine check-ups is a crucial component of effective diabetes management and treatment. One factor influencing adherence is family support. Objective: To determine the relationship between family support and adherence to routine check-ups among diabetes mellitus patients. Methods: The study design employed a correlational analytical approach using a cross-sectional design. The sample consisted of 80 respondents selected via simple random sampling. Data were collected through a family support questionnaire and secondary data (medical records) from the community health center. Data analysis used the Spearman rank test with a significance level of α < 0.05. Results: This study found that 90% of participants had good family support, 10% had adequate family support, 88% adhered to routine check-ups, and 12% did not adhere to routine check-ups. Based on the Spearman’s rho correlation test, the significance value (two-tailed) was 0.001 < 0.05, indicating a significant association between family support and adherence to follow-up visits. Discussion: Family involvement in patient care is crucial for the management and control of diabetes mellitus (DM). Families can foster positive behaviors, such as enhancing motivation and improving adherence among DM patients.